Peningkatan Motivasi Belajar Peserta Didik dengan Menggunakan Pendekatan Pembelajaran Berdiferensiasi di Kelas XI SMA Negeri 2 Rantau Selatan - Sinta Roulina Sihombing (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is Classroom Action Research (PTK) which aims to increase student learning motivation by using a differentiated learning approach in class XI SMA Negeri 2 Rantau Selatan. The problem faced is students' low enthusiasm for learning, such as not being active during lessons, being lazy about doing assignments, and unsatisfactory learning results. Differentiated learning is chosen because it can adapt to students' differences in abilities, interests and learning styles. The research was conducted in two cycles. The research subjects were 29 students of class XI Phase F-3. Data was collected through observation, learning motivation questionnaires, and documentation, then analyzed. The research results show that the differentiated learning approach can increase students' learning motivation. Students become more enthusiastic, active and responsible in learning. Thus, this approach has proven effective in increasing learning motivation in class XI SMA Negeri 2 Rantau Selatan.